Comparative study of anthropometric measurement and body composition between junior soccer and volleyball players from the Serbian national league - Masanovic, B.; Bavcevic, T.; Bavcevic, I. (SportMont, 2019)
The purpose of this study was to describe anthropometric characteristics and body composition of junior soccer and volleyball players from the Serbian National League as well as to make a comparison between them. Seventy-one male athletes were enrolled in this study, divided into three groups: twenty-five soccer players, fourteen volleyball players and thirty-two healthy sedentary subjects. All subjects were assessed for anthropometric measures required for the calculation of body composition variables, using standardized procedures recommended by previous studies. Data was analysed using SPSS and the descriptive statistics were expressed as a mean (SD) for each variable, while the ANOVA and the LSD Post Hoc tests were carried out to detect effects of each type of sport. The results showed that a significant difference was found in variables height, weight, and body fat, but no significant difference was found in the remaining three variables, body mass index, muscle mass or bone content. Volleyball players were significantly taller and heavier than soccer players or subjects from the control group, while there was no significant difference between height and weight of soccer players and subjects from the control group. Subjects from the control group had significantly higher percentage of body fat than both soccer and volleyball players. Soccer players had the lowest percentage of body fat, while subjects from the control group had the highest values of the same variable. Therefore, these findings may give coaches from the region better working knowledge and suggest to them to follow recent selection process methods and to be more careful during the process of talent identification.